KARAKTERISTIK, MOTIVASI DAN NIAT WISATAWAN SURFING DI PANTAI KECAMATAN KUTA UTARA - Ni Putu Windy Pramita; I Wayan Suardana; Luh Gede Leli Kusuma Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2017)
Black sandy beach tourist attraction of Kuta Northen region that is Batu Bolong beach and Batu Mejan beach which has potential a beautifull oncean, sunset, sunbathing and surfingthe purpose of this study was to determinethe characteristics, motivasi, and intentions rating surfing at Kuta Northen beach. The method used observation, questionnaires, interviews, literature study, and documentation. 213 respondens rating surfing with quantitative descriptive and regression linier analisys. The result obtained in this study are based on age characteristics surfing travelers will see the most travelers age between 18-29 years, male gender, country of origin Australia, and is a businessman, a master degree educational level, and marital status is not married. Surfing tourist motivation using push and pull factor with the highest scores on the social interaction. And Intention surfing tourist with the highest score there is positive world of mouth with Variabel tourist have the effect of 13,20% with a probability level of sig. 0,000, the motivation positive and significant efeect on the intention tourist but in small quantities. Therefore to improve the intention tourist come to the beach district of north kuta from the motivation pull and push should also improve the quality of beaches such as keeping the beach becomes the most importans thing that will directly make tourist feel comfortable. advice for managers is to add a lifeguard to keep the beach.